Optimizing bitter gourd (Momordica charantia L.) performance: exploring the impact of varied seed priming durations and zinc oxide nanoparticle concentrations on germination, growth, phytochemical attributes, and agronomic outcomes - Muhammad Waqas Mazhar; Muhammad Ishtiaq; Mehwish Maqbool; Eman A. Mahmoud; Fazal Ullah; Hosam O. Elansary (Cogent Food & Agriculture)
This field study aimed to investigate the potential of zinc oxide nanoparticles (ZnONPs) to enhance various aspects of bitter gourd plant germination, growth, phytochemical composition and yield. Bitter gourd seeds were subjected to soaking in aerated solutions of ZnONPs at concentrations of 50 and 100 ppm for 24 and 48 hours, with hydro-primed seeds serving as the control group. Priming bitter gourd seeds with 100 ppm ZnONPs for 48 hours significantly improved germination, increased the number of fruits per plant, enhanced fruit density, and showed improvements in elevating the plant’s phytochemical profile. Notably, seed priming with 100 ppm ZnONPs for 48 hours resulted in a 29% increase in germination percentage. Furthermore, treatment with 100 ppm ZnONPs for 48 hours exhibited significant enhancements in key parameters such as the number of fruits per plant, fruit density, fruit length and fruit diameter, demonstrating increases of 41%, 29%, 29%, and 42.3%, respectively, compared to the control group. The application of ZnONPs at concentrations of 100 ppm for both 24 and 48 hours to bitter gourd seeds also led to substantial elevations in the plant’s phytochemical profile. Specifically, total phenolic content saw increments of 12% and 27%, total flavonoid content saw increments of 16% and 30%, and total charantin content saw increments of 12% and 29%, respectively, compared to the hydro-priming treatment. The study underscores the operational benefits of employing ZnONPs for seed priming, which positively influences germination, growth, phytochemical composition, and ultimately the yield of bitter gourd plants.